Does women’s anxious jealousy track changes in steroid hormone levels? - Hahn, Amanda C.; DeBruine, Lisa M.; Pesce, Lola A.; Diaz, Andrew; Aberson, Christopher L.; Jones, Benedict C. (Psychoneuroendocrinology, 2020)
•Animal studies suggest anxiety is linked to progesterone in females.•There have been few direct tests of this hypothesis in humans.•Anxious jealousy and endogenous progesterone measured longitudinally in a large sample of women.•No evidence for within-subject effects of progesterone on reported anxious jealousy. Findings for progesterone and anxiety in non-human animals led to the hypothesis that women’s interpersonal anxiety will track changes in progesterone during the menstrual cycle. There have been few direct tests of this hypothesis, however. Consequently, we used a longitudinal design to investigate whether interpersonal anxiety (assessed using the anxious jealousy subscale of the relationship jealousy questionnaire) tracked changes in salivary steroid hormones during the menstrual cycle in a large sample of young adult women. We found no evidence for within-subject effects of progesterone, estradiol, their interaction or ratio, testosterone, or cortisol on anxious jealousy. There was some evidence that other components of jealousy (e.g., reactive jealousy) tracked changes in women’s cortisol, however. Collectively, these results provide no evidence for the hypothesis that interpersonal anxiety tracks changes in progesterone during the menstrual cycle.